Prototyping an Information Management Software - Mårtensson,Johan (2004)
Abstract Titel: Prototyping an Information Management Software - A study of the Handover Tool at SIG Pack Authors: Jonas Andersen, Lund Institute of Technology Johan Mårtensson, School of Economics and Management, Lund University. Tutors: Mats Persson, Department of Construction Management, Lund Institute of Technology, Sweden Leif Edvinsson, Research Policy Institute, Lund University, Sweden Gerhard Burger, Centre of Enterprise Sciences, Swiss Federal Institute of Technology, Zürich, Switzerland Urs Hafen, Head of Business Competence Centre Services, SIG Pack Services, Neuhausen am Rheinfall, Switzerland Issues: There are many examples of projects that have varied and extended different prototyping strategies for developing user interfaces for software applications. Recent studies have also pointed out that prototyping is beneficial in other areas, such as gaining user acceptance and validating requirements. These areas are not thoroughly covered in the literature, which make them interesting to study. The project management in the Handover Project was confident that a prototyping approach should be used for the development of the new Information Management Application, the Handover Tool. Prototyping has not been used in the organisation before. Therefore, there were no guidelines available for such an approach. The project management welcomed a prototyping strategy based on the theory. Purpose: The theoretical purpose is to create a prototyping strategy based on the theory, and evaluate and analyse how this strategy worked in the development of the Handover Tool. The practical purpose of this thesis is to develop prototypes of the Handover Tool. They should be used for communication with the stakeholders of the Handover Project and serve as a specification for the implementation of the final version. Method: Action Research is a method that combines practical problem solving and theoretical contributions. The research has been conducted in two iterative cycles, to separate the theoretical interest from the practical problem solving. Conclusions: The feedback from the workshops with the stakeholders was classified in two terms, type and area. The type is the technique to deliver the feedback, as proposals or as critique. The area is the part of the project or system, which the feedback aims at, conceptual, functional, user interface or technical. It is important to classify the feedback, to be able to prepare and improve the workshops in a more structured way. A categorisation of the feedback should be considered already in the strategy. In recent years the literature has put more attention to the prototyping possibilities besides the usability area. This thesis shows, as well as the literature, that there are more possibilities with prototyping than user interface improvements. The goals that were fulfilled in the prototyping of the Handover Tool were apart from usability improvements; establishment of a dynamic specification, stimulation and experimentation of ideas and establishment of acceptance for the general concept among the critical users. It has been argued that the main reason for the successful prototyping in the handover case was the differentiation between the audience groups, because it facilitated preparation and planning. This differentiation approach should be applicable in many cases and help to make the prototyping more beneficial in a wide range of areas.
Keywords: Prototyping; business process; user acceptance; workshop; feedback; software development; web application; Management of enterprises; Företagsledning, management